Multiplex ligation-dependent probe amplification versus fluorescent in situ hybridization for screening RB1 copy number variations in Egyptian patients with retinoblastoma. (2nd November 2022) - Eid, Ola M.; El Zomor, Hosam; Mohamed, Amal M.; El-Bassyouni, Hala T.; Afifi, Hanan H.; El-Ayadi, Moatasem; Sadek, Sherin H.; Hammad, Saida A.; Salem, Sherine I.; Mahrous, Rana; Fadel, Islam M.; Refaat, Khaled; et al.
ABSTRACT: Background: Retinoblastoma (RB) is the most common primary intraocular malignant tumor in children. RB is mostly caused by biallelic mutations in RB1 and occurs in hereditary and non-hereditary forms according to the "two-hit" theory. RB1 mutations comprise point mutations, indels, large deletions, and duplications. Genetic testing is essential for the comprehensive treatment and management of patients with RB. Aim: The aim was to evaluate RB1 copy number variations (CNVs) using MLPA versus FISH assays in group of Egyptian patients with RB. Results: 16.67% showed an RB1 deletion, abnormal methylation status, or both. Conclusion: Our results suggested MLPA is a fast, reliable, and powerful method and should be used as a first-line screening tool for detecting RB1 CNVs in patients with RB. Moreover, MLPA is advantageous as it evaluates the methylation status/inactivation of RB1, not possible by FISH.